Psychometric properties of the effort-reward imbalance scale in Chinese version for university students - Kequn, Chu; Biao, Li; Shaohua, She (Frontiers in Psychology, 2023)
Objective The main purpose of the study was to translate the Effort-Reward Imbalance Scale for University Students (ERIUS) and assess its psychometric properties in the Chinese cultural context. Methods We translated the original English version of the ERIUS into Chinese and undertook exploratory and confirmatory factor analysis using data collected from university students. The Stress Scale for College Students was selected as the criterion measure to examine the association between psychological stress and effort-reward imbalance. The validity and reliability of the translated version of the ERIUS were also assessed, and a sub-sample of participants (n = 120) completed the measure twice, with a two-week interval to assess test–retest reliability. Result Results of the exploratory factor analysis using data from 314 students showed that the Chinese version of the ERIUS had 14 items and 3 factors: effort, reward and overcommitment. Confirmatory factor analysis using data from 584 students showed that the Chinese version of the ERIUS had adequate structural validity (χ2 = 107.10, df = 32, RMSEA = 0.08, NFI = 0.90, CFI = 0.91, GFI = 0.90, PGFI = 0.62). Conclusion The Chinese version of the Effort-Reward Imbalance Scale for University Students has adequate psychometric properties in the Chinese cultural context and can be used as an effective tool to measure psychosocial stress of university students in China.